2010
DOI: 10.1177/0333102410365106
|View full text |Cite
|
Sign up to set email alerts
|

Medium-dose riboflavin as a prophylactic agent in children with migraine: A preliminary placebo-controlled, randomised, double-blind, cross-over trial

Abstract: In this group of children with migraine, there is no evidence that 50 mg riboflavin has a prophylactic effect on migraine attacks. We found some evidence that 50 mg riboflavin may have a prophylactic effect on interval headaches that may correspond to mild migraine attacks or tension-type headache attacks in children with migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 26 publications
1
60
0
1
Order By: Relevance
“…30,[34][35][36][37] Based on emerging evidence, some clinicians also recommend dietary supplements that decrease inflammation (omega-3 fatty acids) and dietary supplements, such as riboflavin, magnesium, and coenzyme Q10. [38][39][40][41][42][43][44] However, some clinicians are not familiar with these therapies; therefore, they do not use them and do not inquire about them. So, little is known about the extent of their impact or use by their patients who experience HA.…”
Section: Resultsmentioning
confidence: 99%
“…30,[34][35][36][37] Based on emerging evidence, some clinicians also recommend dietary supplements that decrease inflammation (omega-3 fatty acids) and dietary supplements, such as riboflavin, magnesium, and coenzyme Q10. [38][39][40][41][42][43][44] However, some clinicians are not familiar with these therapies; therefore, they do not use them and do not inquire about them. So, little is known about the extent of their impact or use by their patients who experience HA.…”
Section: Resultsmentioning
confidence: 99%
“…This need for an adequate washout period at the time of crossing over is now acknowledged, and has become standard in more recent trials. 26 The authors of the original study concluded that "propranolol prophylaxis is a safe and effective therapy for migraine prophylaxis." 11 Our study adds little to this.…”
Section: Discussionmentioning
confidence: 99%
“…Other prophylactic medicines are topiramate, valproic acid, levetiracetam, gabapentin, lamotrigine, zonisamide, pregabalin, cyproheptadine, and propranolol [2,87,[89][90] . Among these, only topiramate is approved by FDA, in adolescents 12-17 years of age [91] .Neutraceuticals including riboflavin, coenzyme Q10, butterbur and magnesium showed some efficacy [1,[92][93][94] . Onabotulinumtoxin A is FDA-approved medication for a chronic migraine in adults and showed improvement in disability scores and headache frequency in pediatric chronic daily headache patients and in pediatric chronic migraine [95] .…”
Section: Table2 Drugs Used In the Management Of Migraine Headaches Imentioning
confidence: 99%